PERILAKU PETUGAS KESEHATAN DALAM PENANGANAN LIMBAH MEDIS DI RUMAH SAKIT IBU DAN ANAK PEMERINTAH ACEH - , Heriansyah; , Prof. Dr. dr. Adi Heru Sutomo, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Waste Produced by the activities of the hospital can bring out the high risk for health if canât managed properly and correctly. The especially infectious waste (15% until 25%) from total of waste produced by the hospital. In Ibu dan Anak hospital Aceh Government still have problems of mixing medical and non medical waste. Particularly infectious medical waste is not managed properly. Separation of hazardous wastes from all wastes at the site of waste is one key for good waste disposal and this is strongly be affected by the behavior of health workers who work on waste-producing unit in the hospital. Goal: to know the relationship among knowledge, attitude, hospital policy and availability of medical waste treatment facilities with behavioral of health workers in handling of waste in Ibu dan Anak hospital Aceh Government. Method: the design of this study is observational using cross sectional survey design with the total of respondents was 80 persons. Result: there are positive and significant relationship of knowledge, attitude, hospital policy and availability facility with behavioral of health worker in the handling of waste (P<0.05) and low levels of closeness of relationship. Conclusions: attitude variables provide a very large effective contribution (17.858%) against the behavior of health workers in the handling of medical waste.